Dari Masa ke Masa: Memahami Evolusi Akuntansi dan Masa Depan Profesi Akuntansi - Nurul Karimah; Asih Kusuma Watie; Siti Aisah; Gunawan Aji (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The history of accounting dates back to the beginning of human civilization, when transactions involving the purchase and sale of goods were first recorded, summarized, and reported. Each era makes a significant contribution to the field of accounting science. Considering how the role of accountants is changing in the digital era, accountants also need to have a plan to survive any revolution or change. This research aims to reveal the history of accounting in the past and what the future of accounting will be like. Using descriptive qualitative methods with a literature study approach, this research identifies relevant sources such as books and scientific journals, which are related to the focus and topic of the research. Accounting is a field that has evolved over time. Accounting in the past is history, accounting in the present is reality, and accounting in the future is a dream or fantasy that can become a reality